INOVASI OLAHAN BABY CUMI KERING ASIN DAN ABON IKAN SEBAGAI WIRAUSAHA ISTRI NELAYAN DI DESA TERAPUNG KECAMATAN MAWASANGKA KABUPATEN BUTON TENGAH - Safrin Edy; Wa Ode Al Zarliani; Aliani Aliani; Maghfira Pathiha; Abdul Hadi Bone; Bahtiar Hamar; Wa Ode Sitti Cahyani; Salmatia Salmatia; Sariafriani Amran (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
The potential of fishery resources in the Terapung Village" Mawasangka District, Central Buton Regency is one of the valuable assets, but the income level of fishermen often occurs in the marketing and processing process of the catch. Lack of knowledge and ability of fishermen in maximizing the catch is one of the contributing factors . Therefore, the purpose of Community Service activities is to help partners in processing salted dried baby squid and fish shredded products, packaging and marketing products, inspiring people to be more confident in developing businesses to improve community welfare, creating collaboration between higher education institutions with society. The method of implementing activities with a community empowerment system is carried out through a transfer of knowledge and technology model for processing salted dried squid and shredded fish in two stages. The first is the provision of materials and training to students before going down to the location so that they can transfer skills to the community or target groups properly and correctly. The second is training on processing dried squid and shredded fish which begins with the presentation of material to add insight to the target group, namely the business group of fishermen's mothers and then continues with the practice of processing salted dried squid and shredded fish. The areas that are jointly resolved in this activity are product processing innovations which include: basic processing techniques for product raw materials, formulation techniques for processed product ingredients, packaging and labeling techniques, marketing management and business feasibility analysis. Indicators of the success of community service can be seen from the processed products of salted dried squid and shredded fish with flavor variants that have been packaged with labeling, marketing management and business feasibility analysis. After the implementation of the activity, the group that has been formed is expected to continue the program of activities by opening a business for processing squid and shredded fish. Based on the results of the implementation of community service activities, it can be concluded that the stages of the method carried out have succeeded in achieving the objectives of the activity, namely: 1). The group of mothers has been able to process salted dried baby squid and shredded fish. 2). The group of mothers has been able to package and market processed products, although online marketing still needs assistance. 3. This activity inspires the community to be more confident in developing businesses to improve the welfare of coastal communities. 4. This activity is able to create cooperation between higher education institutions and the community.